NUTRITIONAL STATUS AMONG CHILDREN UNDER 5 YEARS OLD IN TWO COMMUNES IN YEN DINH DISTRICT, THANH HOA PROVINCE IN 2022 - Đinh, Thi Kim Anh; Ngô, Thị Đặng; Ninh, Thị Nhung; Lê, Đức Cường (Tạp chí Dinh dưỡng và Thực phẩm, 2024)
Aims: To identify the nutritional status of children under five years in Yen Tam and Dinh Hoa communes of Yen Dinh district, Thanh Hoa province in 2022. Methods: A cross-sectional study was conducted on 733 children aged under 5 years between January and May of 2022 in the communes. The nutritional status of the children was classified using World Health Organization standards in 2006. Results: The stunting rate of the children was 22.1%, of which 19.4% were moderately stunted and 2.7% were severely stunted. 34% of the chilldren suffered from at least one form of malnutrition (stunting, wasting and underweight).The rate of manutrition was higher in boys as compared to girls and the highest rate of malnutrition was found in the group aged 25-48 months. Conclusion: Malnutrition was predominant in the communes, especially stunting. It is important to pose in priotity the interventions to reduce malnutrition rates and focus on solutions to prevent stunting.